Synthesis of Apoptotic New Quinazolinone-Based Compound and Identification of its Underlying Mitochondrial Signalling Pathway in Breast Cancer Cells - Zahedifard, M.; Faraj, F.L.; Paydar, M.; Looi, C.Y.; Hasandarvish, P.; Hajrezaie, M.; Kamalidehghan, B.; Majid, N.A.; Khalifa, S.A.M.; Ali, H.M.; Abdulla, M.A.; El-Seedi, H.R. (Bentham Science Publishers, 2015)
The anti-carcinogenic effect of the new quinazolinone compound, named MMD, was tested on MCF-7 human breast cancer cell line. The synthesis of quinazolinone-based compounds attracted strong attention over the past few decades as an alternative mean to produce analogues of natural products. Quinazolinone compounds sharing the main principal core structures are currently introduced in the clinical trials and pharmaceutical markets as anti-cancer agents. Thus, it is of high clinical interest to identify a new drug that could be used to control the growth and expansion of cancer cells. Quinazolinone is a metabolite derivative resulting from the conjugation of 2-aminobenzoyhydrazide and 5-methoxy-2-hydroxybenzaldehyde based on condensation reactions. In the present study, we analysed the influence of MMD on breast cancer adenoma cell morphology, cell cycle arrest, DNA fragmentation, cytochrome c release and caspases activity. MCF-7 is a type of cell line representing the breast cancer adenoma cells that can be expanded and differentiated in culture. Using different in vitro strategies and specific antibodies, we demonstrate a novel role for MMD in the inhibition of cell proliferation and initiation of the programmed cell death. MMD was found to increase cytochrome c release from the mitochondria to the cytosol and this effect was enhanced over time with effective IC50 value of 5.85 ± 0.71 μg/mL detected in a 72-hours treatment. Additionally, MMD induced cell cycle arrest at G0/G1 phase and caused DNA fragmentation with obvious activation of caspase-9 and caspases-3/7. Our results demonstrate a novel role of MMD as an anti-proliferative agent and imply the involvement of mitochondrial intrinsic pathway in the observed apoptosis.